Experimental Test of The Gap Reinforced Fastened Connection (GRFC): A highly stiff and ductile reinforced connection concept with reduced pinching for timber structures. (15th January 2022) - Araya, Raúl; Montaño, Jairo; Guindos, Pablo
Highlights: A new reinforcing connection concept for timber structures is presented. An assumption of double embedding fasteners is used for stiffness calculations. Improvements in stiffness, ductility and seismic behavior are presented. Influence of diameter, spacing, strength degradation and gap size are investigated. Abstract: This paper presents a new reinforced connection concept entitled Gap Reinforced Fastened Connection (GRFC), from the theoretical formulation of the concept to a mechanical characterization of an example application through monotonic and cyclic tests. The proposed reinforcement incorporates a steel plate bonded with epoxy to the wood, separating another steel plate with a gap at the shear plane. The failure mechanism consists of enforcing the development of plastic hinges of fasteners at this gap interface, avoiding the crushing in the wood and obtaining a behavior dependent only on the properties of the fasteners and their interaction with the reinforcement plates. The results of different gap sizes and fastener diameters were reported and discussed. Improvements of the stiffness-ductility ratio were achieved, depending on the fastener diameter and gap selected. From ductility values obtained in the cyclic performance it was found that for connections with slender fasteners, it was easier to obtain a highly ductile classification according to Eurocode 8. Also, cyclic tests have shown that, energy dissipation is most effective when multiple small diameter fasteners are used, reducing the pinching and impairment of strength in the connection. A reduced spacing between fasteners can be obtained through the incorporation of GRFC and using the requirements prescribed for steel structures instead of timber, eliminating the risk of grouping effects that trigger brittle failure modes. The research gives an example of the application of the concept, which allows to redefine the traditional timber connection design used in hold-down connections, in addition to laying the groundwork for its application in other types of connections.